Bail Financial Sharing (BFS): A Financial Subsystem of Rastin PLS Banking - Bidabad, Bijan (International Journal of Islamic Banking and Finance Research, 2019)
To cover producers and consumers against future prices fluctuation risk, depositors can forward-purchase raw materials or products to be delivered at a specified time in the future through Bail Financial Sharing (BFS). Bail Financial Sharing is a subsystem of Rastin Profit and Loss Sharing (PLS) banking system, and in this regard, instructions, organization and application methods, and electronic devices and contracts are similar to the context defined in the Base System of Rastin PLS banking system. Bail Financial Sharing (BFS) enjoys from Bail Certificate innovation, which can play an important role in stabilizing and increasing efficiency of money and financial markets. Depositor (financer) receives digital Bail Certificate for this kind of participation, which is negotiable in the secondary Rastin Certificate market. Regarding the characteristics of this certificate and its clear substantial differences with futures derivative, it prevents unreal paper markets formation. The latest owner of the certificate is the owner of the commodity. Moreover, the depositor can ask the bank that the entrepreneur sells the commodity and pays the money –instead of commodity- to him at the end of the contract.